Micro and Small Enterprises of Former Combatants: Behind Economic Contributions and Problems to Transforming Peace in the Affected Conflict Community of Aceh - Abubakar, Muhammad Bin; Abubakar, Ayesah Uy; Zainal, Suadi; Safrina, Lia (Universitas Teuku Umar, 2025)
This study analyzed the positive effects behind micro and small enterprises (MSEs) empowerment programs of the former combatants - the Free Aceh Movement (GAM) despite its problem, on transforming Aceh conflict to a positive peace. MSEs play a critical role in contributing not only to economic empowerment but also conflict transformation and sustaining peace especially during the post peace agreement, that granted Aceh a form of decentralization of power from central government, with a significant degree of political and economic autonomy. Indonesia. Although the MSEs in rural Aceh Province most of them failed, they have positively contributed to the sustainable peace in the region. Based on this assumption, this study explores the ex-combatant's experience with the MSEs program within the framework of decentralized power, and how the program gradually brought them back into the community. In-depth interviews, and field work observation, were the main techniques of the data collection. The data analysis was done using thematic analysis. The study found that autonomy and decentralization has created new political marketplace. MSEs that were set up in small groups of former combatants, civilian victims and other interested community members, was used to build patronage network and that led to their failure. However, the interactions occurring in operating these MSEs have re-established the relationships among the former combatants, victims, and ordinary people that were broken during the conflict. Thus, MSEs gradually reintegrated those ex-combatants into the community.